DEVELOPMENT OF BUSINESS ACTIVITY IN THE AREAS OF SMALL AND MEDIUM BUSINESSES AS POSSIBLE (British Journal of Global Ecology and Sustainable Development, 2024)
This article develops the activities of small businesses and private businesses operating in various sectors of the national economy, and creates favorable conditions for small and medium-sized businesses in the regions.